Antonia Raeburn (1934–2021): an appreciation. Issue 3 (16th April 2022) - Purvis, June
ABSTRACT: Antonia Raeburn (1934–2021) was the author of a well-known book titled The Militant Suffragettes, published in 1973, which gave an account of the suffragette struggle in Edwardian Britain for the parliamentary vote for women. The book was important in that it focused on the rank-and-file members of the Women's Social and Political Union (WSPU), founded in 1903 by Emmeline and Christabel Pankhurst together with some local socialist women, and included unique interviews with aged suffragettes who reminisced about the past. In this book and a second one, The Suffragette View, published in 1976, Antonia stressed that it was critical for women's voices to be heard at a time when few historians were researching this women's movement and those who did were often hostile or dismissive of it. An author without the security of an academic job and the contacts that it brings, she ploughed a lonely field.